Serratia fonticola, pathogen or bystander? A case series and review of the literature - Abdullah Aljorayid; Roberto Viau; Laila Castellino; Robin L.P. Jump (IDCases, 2016)
Serratia fonticola is an unusual human pathogen, previously described primarily as causing skin and soft tissue infections following trauma. There is little information in the literature about its treatment or susceptibilities. We describe the case of a 67-year-old male with paraplegia who developed urosepsis due to S. fonticola. Blood and urine cultures obtained prior to the initiation of antimicrobials both grew S. fonticola. The patient completed a 15-day course of antimicrobials and had an uneventful recovery. We reviewed 17 other patients with clinical cultures positive for S. fonticola. Of these, 11 isolates were from the genitourinary system, most often as part of a polymicrobial culture. The majority of the other organisms recovered were recognized pathogens from the Enterobacteriaceae family. The cases suggest that when recovered in conjunction with other organisms, S. fonticola does not lead to enhanced virulence or worse clinical outcomes and may be a bystander. When detected alone, which is a rare occurrence, S. fonticola may function as a human pathogen.